Knowledge of elderly women about the use of psychotropics - Fabrícia Araújo Prudêncio; Lidya Tolstenko Nogueira (Rev Rene, 2013)
The process of aging can result in diseases and the need for psychotropic medication. This exploratory and descriptive research with qualitative approach aimed to describe the knowledge of the elderly women about the use of such medication. We interviewed 18 elderly subjects, from July to August 2009, registered in the Family Health Strategy that had been using benzodiazepine and / or antidepressants. The data were organized through Bardin’s technique of content analysis. This research showed that the elderly knew the therapeutic indication of the psychotropic medication, how to distinguish the adverse reactions and reported addiction, mainly to benzodiazepine. We concluded that elderly people assisted by the Family Health Strategy acquired knowledge about psychotropic drugs in their everyday experience and that it is necessary to extend discussions on the topic, as well as the formulation of guidelines aimed at the use of psychotropic drugs by the elderly.